2022
DOI: 10.3390/nu14204438
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Awareness of the Degree of Industrial Food Processing and the Association with Healthiness—A Pilot Study

Abstract: Consumption of ultraprocessed foods (UPFs) has been associated with lower diet quality, obesity, and adverse health effects. Not much is known about how consumers evaluate the degree of processing of a food product and how they relate this to healthiness. An online questionnaire was completed by a total of 277 Dutch, 204 Italian, and 181 Brazilian consumers. Consumers were aged 18–65 year, mean 38 ± 13 year, 31% were males, and 71% were highly educated. Pictures of several common food products were evaluated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…The results from these three examples confirm that there is a limited knowledge of consumers about food processing (Bolhuis et al. , 2022), however they have different perceptions and expectations from the processing conditions.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…The results from these three examples confirm that there is a limited knowledge of consumers about food processing (Bolhuis et al. , 2022), however they have different perceptions and expectations from the processing conditions.…”
Section: Resultsmentioning
confidence: 52%
“…The results from these three examples confirm that there is a limited knowledge of consumers about food processing (Bolhuis et al, 2022), however they have different perceptions and expectations from the processing conditions. For consumers industrially processed foods are highly different from artisanal and home-made food processing, which are perceived by them having less additives and processing steps.…”
Section: Consumer Perception On Apple Processingmentioning
confidence: 51%
“…The concept of UPF is complex, and the effect of an "ultraprocessed" label may depend on consumers' understanding of it. A few qualitative studies in Latin America have found that the idea conveyed by the term "ultraprocessed" is reasonably well understood and associated with unhealthfulness [64][65][66], while studies in Europe have uncovered more variation in clarity about the concept [67,68]. Although, to our knowledge, no studies have assessed understanding of the term among US consumers yet, one study has shown that the perception of more processed foods as less healthful is lower among US consumers compared to consumers in Canada, Australia, the UK, and Mexico [69].…”
Section: Discussionmentioning
confidence: 99%
“…The commercialization of ultra -processed foods (UPF) worldwide is constantly growing, despite the fact that consumers know that they can be harmful to health [1]. Their consumption is associated with poor diet quality, but there is little information on how consumers estimate the level of food processing and how much influence they have on health [2 ]. The perception of ultra -processed foods is negative, to the point that they are often referred to as unreal foods [3], so different industries seek to reduce the caloric content of their ultra -processed foods by creating new formulas and replacin g caloric sugars with calorie-free sweeteners to thus change consumers' perception of how harmful their product they consume is [4].…”
Section: Introductionmentioning
confidence: 99%